Hypersensitivity of the vimentin cytoskeleton to net-charge states and Coulomb repulsion - Unger, Bret A; Wu, Chun Ying; Choi, Alexander A; He, Changdong; Xu, Ke (bioRxiv, 2024)
As with most intermediate filament systems, the hierarchical self-assembly of vimentin into nonpolar filaments requires no nucleators or energy input. Utilizing a set of live-cell, single-molecule, and super-resolution microscopy tools, here we show that in mammalian cells, the assembly and disassembly of the vimentin cytoskeleton is highly sensitive to the protein net charge state. Starting with the intriguing observation that the vimentin cytoskeleton fully disassembles under hypotonic stress yet reassembles within seconds upon osmotic pressure recovery, we pinpoint ionic strength as its underlying driving factor. Further modulating the pH and expressing differently charged constructs, we converge on a model in which the vimentin cytoskeleton is destabilized by Coulomb repulsion when its mass-accumulated negative charges (-18 per vimentin protein) along the filament are less screened or otherwise intensified, and stabilized when the charges are better screened or otherwise reduced. Generalizing this model to other intermediate filaments, we further show that whereas the negatively charged GFAP cytoskeleton is similarly subject to fast disassembly under hypotonic stress, the cytokeratin, as a copolymer of negatively and positively charged subunits, does not exhibit this behavior. Thus, in cells containing both vimentin and keratin cytoskeletons, hypotonic stress disassembles the former but not the latter. Together, our results both provide new handles for modulating cell behavior and call for new attention to the effects of net charges in intracellular protein interactions.